Back Cover: On‐Site Non‐enzymatic Orthogonal Activation of a Catalytic DNA Circuit for Self‐Reinforced In Vivo MicroRNA Imaging (Angew. Chem. Int. Ed. 45/2022). Issue 45 (25th October 2022) - He, Shizhen; Yu, Shanshan; Li, Ruomeng; Chen, Yingying; Wang, Qing; He, Yuqiu; Liu, Xiaoqing; Wang, Fuan
Abstract : A non‐enzymatic circuitry activation strategy can realize an orthogonally controlled catalytic DNA (CCD) circuit through multiple molecular recognition events and progressively accelerated signal amplification, as reported by Fuan Wang and co‐workers in their Research Article (e202206529) . The on‐site activated CCD circuitry system has considerable potential for high‐precision in vivo imaging of low‐abundance microRNA.